UJI TOKSISITAS BUAH BERUWAS LAUT (Scaevola taccada) DENGAN METODE BRINE SHRIMP LETHALITY TEST (BSLT) - Nisa, Kharisma; Putri, R. Marwita Sari; Apriandi, Azwin (Marinade, 2021)
Beruwas Laut fruit (Scaevolla taccada) comes from the beach Tanjung Siambang, Dompak, Bukit Bestari, Tanjungpinang City, Kepulauan Riau. This study aims to determine the level of toxicity and active compounds in Beruwas Laut fruit. Fruit extraction is carried out in two ways, namely crude extraction and pure water extraction without using solvents. Each extract was tested for its toxicity against shrimp larvae Arthemia salina Leach. The mortality of A. salina larvae was analyzed using Microsoft Excel probit analysis to determine the LC50 value of each fruit extract. The result showed that the toxicity test results of the crude extract of Beruwas Laut fruit 1908,542 ppm and the extract of pure Beruwas Laut was 1654,263 ppm. The results of the phytochemical test showed that the crude extract and pure water extract contained only the preductive sugar.